A Prospective Study of Post-operative Complications Following Stapled Haemorrhoidectomy - Rahman, Nazmin; Hoque, Muhammad Anwarul (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Haemorrhoids is one of the most common anorectal disorders. Stapled haemorrhoidectomy (SH) is newly developed method for the surgical management of Haemorrhoids. Objective: To evalute postoperative complications followed by Stapled haemorrhoidectomy. Methods: A prospective observational study was conducted among the patients with haemorroid those who got admitted in different surgery units in the department of surgery in Shaheed Suhrawardy Medical College Hospital, Dhaka from 01 December 2015 to 31 May 2016. A total of 60 patients were selected following convenient sampling technique. Data were collected by face to face interview using a structured questionnaire and check list. All completed questionnaires were validated manually and data were analyzed by using descriptive and inferential statistics with SPSS 19.0. Results: In this study, immediate complications (first week) were: bleeding (8.3%), urinary retention (5.0%), moderate pain (5.0%), pruritus (5.0%) and submucosal abscess (1.7%). The most common complication after 1 week was mild pain (8.3%), stenosis (5%), flatus incontinence, recurrence of hemorrhoids in 3.3% and bleeding was (3.3%). Recurrent hemorrhoids were treated by ligation in 40% and by Milligan-Morgan procedure in 32%. Anal stenoses were treated by dilatation in 55% and by anoplasty in 45%. It was revealed from study that among the patients treated with SH 21.6% had immediate complications followed by 24.3% had late complications. Conclusion: Prevention is the best treatment of haemorrhoids. Stapled haemorrhoidectomy is safe with many short-term benefits like less post-operative pain, early return from hospital and early return to their normal activities. Like other modalities it is also associated with a long-term risk of hemorrhoid recurrence and the symptom of prolapse. However, this method is well accepted and comfortable for the patients. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 57-60